Penggunaan Etanol Hasil Pengolahan Sampah Pasar Buah Sebagai Antiseptik untuk Menurunkan Angka Kuman Usap Tangan - Sarjito Eko Windarso; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2013)
Decayed and rotten fruits still contain amylum (carbohydrate) and glucose (sugar) which can be converted into ethanol by fermentation process which is followed by distillation. The ethanol furthermore can be used as antiseptic and ingredient for hand washing and hand cleansing. To know the ability of the ethanol in reducing hand swab microbe number, an experiment which was employing post-test only with control group design was conducted and comparing two ethanol concentrations. The fruit waste processed in this study were obtained from the main fruit market in Gamping, Sleman, while the examination of amylum and glucose concentration, as well as the examination of hand microbe number, were conducted in the health laboratory office of Yogya-karta Province. Descriptively, the hand microbe number yielded from both ethanol concentrations were lower than that from control group which were not washed and cleansed. The microbe number from the hands which were washed by 90 % and 100 % ethanol were 44,90 % and 79,68 % lower in average, compared with those in the control group. However, the mann-whitney non-parametric statistical test showed that only the microbe numbers between control group and the 100 % ethanol concentration group which was significantly different (p value=0,040).